Hitler's northern utopia : building the new order in occupied Norway - Stratigakos, Despina (Princeton University Press, 2020)
Between 1940 and 1945, German occupiers transformed Norway into a vast construction zone. This remarkable building campaign, largely unknown today, was designed to extend the Greater German Reich beyond the Arctic Circle and turn the Scandinavian country into a racial utopia. From ideal new cities to a scenic superhighway stretching from Berlin to northern Norway, plans to remake the country into a model “Aryan” society fired the imaginations of Hitler, his architect Albert Speer, and other Nazi leaders. In Hitler’s Northern Utopia, Despina Stratigakos provides the first major history of Nazi efforts to build a Nordic empire―one that they believed would improve their genetic stock and confirm their destiny as a new order of Vikings.